A Scientist-practitioner Model for Inclusive Education: Supporting Graduate Students to Conduct Systematic Reviews for Evidence-based Practice - Roseanna Bourke; Judith Loveridge (New Zealand Journal of Teachers' Work)
Evidence-based practices and programmes are premised on the assumption that research plays a role in determining ‘what works’ for whom, and when. Governments require evidence-based practices and policies in education to service the dual purpose of maximising or rationalising their funding and to ensure children and young people access the type of services most likely to facilitate successful inclusion through supporting positive learning, social and behaviour outcomes. Subsequently, this also means practitioners and specialist teachers need to access the best available evidence to answer their questions of practice. Postgraduate students in education need to become critical consumers of systematic reviews, as well as knowing how to actively engage in them, when determining how they ensure young people’s learning opportunities are inclusive and maximised. This article explores the process of engaging postgraduate students in an Evidence-based Practice in Education course within an Education Faculty, undertaking systematic reviews around clinically relevant questions.